2004
DOI: 10.1080/16501970410023443
|View full text |Cite
|
Sign up to set email alerts
|

Performance changes for patients with chronic obstructive pulmonary disease on long‐term oxygen therapy after physiotherapy

Abstract: Patients with chronic obstructive pulmonary disease on long-term oxygen treatment may improve their walking distance, experience less dyspnoea and improve activity of daily living ability with an early rehabilitation programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…The studies included examined the effect of adjuvant therapy in addition to an exercise program, 5,11,12,28,29,44,47 they compared exercise with no intervention 21,33 or another treatment modality, 9,19,20,22,25,46 and a few compared the effects of different exercise approaches. 32,40,52 When exercise was applied across conditions, all but 1 study showed improvement within both treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…The studies included examined the effect of adjuvant therapy in addition to an exercise program, 5,11,12,28,29,44,47 they compared exercise with no intervention 21,33 or another treatment modality, 9,19,20,22,25,46 and a few compared the effects of different exercise approaches. 32,40,52 When exercise was applied across conditions, all but 1 study showed improvement within both treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…In nine (81.8%) out of 11 trials, effect estimates exceeded the MID of the Chronic Respiratory Questionnaire establishing large and patient important effects of this intervention [21,[34][35][36][37][38][39][40][41][42][43]. In contrast, assuming 54 m for a relevant change in 6MWD only three (15.8%) out of 19 trials showed effects above this threshold [21,[34][35][36][37][38][39][40][41][42][44][45][46][47][48][49][50][51][52]. This inconsistency between the interpretation of effects on HRQL and 6MWD may raise the suspicion that 54 m may present an exceedingly high estimate for an important change.…”
Section: Puhanmentioning
confidence: 99%
“…In addition, there some evidence from small studies that exertion-related hypoxemia is associated with reduced longevity in COPD [186, [209][210] and an analysis of the original NOTT data showed that patients who could take advantage of ambulatory oxygen by improving their exercise levels had better survival and fewer hospitalizations compared to those who used only stationary oxygen and had lower activity levels [111]. Finally, HRQoL is closely linked to exercise capacity in COPD which tends to decrease with time [185, [211][212], and although not well investigated, there is some data suggesting that LTOT, particularly when combined with pulmonary rehabilitation and maintenance may prevent this deterioration in exercise endurance capacity in certain patients with COPD [39,65,165,[213][214].…”
Section: Role Of Ambulatory Oxygen In Chronically Hypoxemic Patients mentioning
confidence: 98%